2016
DOI: 10.1016/j.biomaterials.2015.11.048
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-specific theranostic nanoplex for combination of TRAIL gene and 5-FC prodrug therapy of prostate cancer

Abstract: Metastatic prostate cancer causes significant morbidity and mortality and there is a critical unmet need for effective treatments. We have developed a theranostic nanoplex platform for combined imaging and therapy of prostate cancer. Our prostate-specific membrane antigen (PSMA) targeted nanoplex is designed to deliver plasmid DNA encoding tumor necrosis factor related apoptosis-inducing ligand (TRAIL), together with bacterial cytosine deaminase (bCD) as a prodrug enzyme. Nanoplex specificity was tested using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 51 publications
(52 reference statements)
0
36
0
Order By: Relevance
“…17 Higher uptake of PSMA targeted particle was detected in PSMA overexpressing PC3-PIP human prostate cancer xenografts compared to isogenic low PSMA expressing PC3-Flu human prostate cancer xenografts, while there was no difference observed with non-targeted particle. 17 The PSMA targeting moiety has been used in separate studies in combination with the bCD-siRNA nanoplex described earlier to achieve PSMA specific delivery of siRNA or cDNA in combination with a prodrug enzyme in vivo 18 for theranostic imaging of prostate cancer. 18a …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Higher uptake of PSMA targeted particle was detected in PSMA overexpressing PC3-PIP human prostate cancer xenografts compared to isogenic low PSMA expressing PC3-Flu human prostate cancer xenografts, while there was no difference observed with non-targeted particle. 17 The PSMA targeting moiety has been used in separate studies in combination with the bCD-siRNA nanoplex described earlier to achieve PSMA specific delivery of siRNA or cDNA in combination with a prodrug enzyme in vivo 18 for theranostic imaging of prostate cancer. 18a …”
Section: Introductionmentioning
confidence: 99%
“…17 The PSMA targeting moiety has been used in separate studies in combination with the bCD-siRNA nanoplex described earlier to achieve PSMA specific delivery of siRNA or cDNA in combination with a prodrug enzyme in vivo 18 for theranostic imaging of prostate cancer. 18a …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies conjugated to the enzyme, as well as viral vectors and non-viral vectors, have been used to achieve this goal (6-13). Recent studies have demonstrated prostate cancer cell-specific nanoparticle delivery of bCD to tumor xenografts by specific targeting of prostate-specific membrane antigen that resulted in improved tumor control (13,14) following localized conversion of 5-FC to 5-FU.However, many types of cancer do not express cancer cell-specific surface receptors or antigens, making it important to determine the effect of 5-FU formed from bCD in the absence of targeted delivery. The therapeutic effect of bCD/5-FC in a metastatic disease setting remains sparsely evaluated (15-17).…”
mentioning
confidence: 99%
“…Monoclonal antibodies conjugated to the enzyme, as well as viral vectors and non-viral vectors, have been used to achieve this goal (6-13). Recent studies have demonstrated prostate cancer cell-specific nanoparticle delivery of bCD to tumor xenografts by specific targeting of prostate-specific membrane antigen that resulted in improved tumor control (13,14) following localized conversion of 5-FC to 5-FU.…”
mentioning
confidence: 99%